Implementation of a Virtual Laboratory Practical Class (VLPC) module in pharmacology education - J. Cheesman, Matthew; Chen, Steven; Manchadi, Mary-Louise; Jacob, Teague; F. Minchin, Rodney; A. Tregloan, Peter (Pharmacognosy Communications)
The Virtual Laboratory Practical Class (VLPC) computer program is a resource aimed at improving practical laboratory performance and understanding in a second-year pharmacology student cohort. In our evaluation of the program, half of the 233 students were provided access to the VLPC before their laboratory session and half after the completion of their experiment. Surveys were conducted to gauge student perception and understanding of the laboratory experiment. In addition, data measuring student completion times for the laboratory task were collected. Students who used the VLPC before the class reported an increase in their confidence in successfully completing the live practical experiment. They also showed a significant decrease in the mean completion time for the real laboratory session. No effect of the VLPC on assignment scores was observed, however this is likely due to the content of the program, which comprised only a very minor portion of these assessable laboratory reports. While some operational issues affected students’ use and engagement in the early stages of the project, students reported benefits to their practical skills and understanding, and perceived the VLPC as a realistic and useful depiction of the laboratory environment.
Keywords: computer simulations; virtual reality; human-computer interface; interactive learning environments